Implementasi Media Booklet Tentang Pendewasaan Usia Pernikahan (PUP) Bagi Remaja di Gereja GBKP KM 8 Medan - Ingka Kristina Pangaribuan; Eva Ratna Dewi; Dewi Sartika Hutabarat; Rismalia Tarigan; Ade Rachmat Yudiyanto; Edi Subroto; Maulidya Khairani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The increasing age of marriage (PUP) is an action taken by the government to increase the age of first marriage, so as to achieve a healthy reproductive age for women of 2o years and for men of 25 years. With a total of 25.53 million incidents of child marriage throughout the world, Indonesia ranks fourth in child marriage statistics (UNICEF, 2023). One of the big problems related to violations of children's rights is child marriage. Based on data, almost 1 in 9 women get married and have children before the age of 18. Therefore, initiatives to stop child marriage are very important. According to data from the Central Statistics Agency (BPS), in 2022, 33.76% of Indonesian teenagers will marry for the first time at the age of 19 to 21 years. The implementation of the service was carried out using Booklet media containing about maturing the age of marriage and the impact of early marriage which was carried out pre and post to determine teenagers' knowledge about PUP. The number of service targets is 60 people. Place of implementation at GBKP Church Km 8 Medan. The results obtained before being given the Booklet , the majority of teenagers had poor knowledge about PUP, 47 people (78.3%) and after being given the Booklet , the majority of teenagers had good knowledge, 57 teenagers (95.0%). During the implementation of the service, teenagers were very enthusiastic about participating and almost all teenagers understood about PUP.